The legal and real situation of woman worker in the rural area - Ferrante, Vera Lúcia Silveira Botta (2009)
The article tries to discuss the situation of woman's work in the rural area, starting from the relation of questions connected to labour action, sindicalism of woman and the conscience levei about rights and her life conditions.